The Effects of Freeze–Thaw Cycles on Methane Emissions From Peat Soils of a High-Altitude Peatland - Yang, Zao; Zhu, Dan; Liu, Liangfeng; Liu, Xinwei; Chen, Huai (Frontiers in Earth Science, 2022)
The Tibetan Plateau, which embodies the largest area of frozen ground in mid- to- low latitudes of the world, has been experiencing rapid permafrost degradation and freeze-thaw change during the past decades. However, the response and potential feedback of the methane flux from peatlands on the Tibetan Plateau with respect to freeze-thaw cycles (FTCs) remains unknown. In this study, we collected peat soils from the largest peatland complex on the Tibetan Plateau to examine the methane emissions under simulated FTCs on a diurnal basis. In incubation experiments of 15 days, two freeze-thaw temperature ranges of -5 °C to 4 °C (mild) and -15 °C to 4°C (intense) were applied to two sets of peat soil samples, each of them was characterized by 100% or 80% maximum water holding capacity (MWHC).The results showed that the peak of methane emission from the peat soil occurred after the first freeze-thaw cycle (FTC1), with the highest reaching a value of 0.103mg·kg-1·h-1. Generally, the cumulative methane emissions had been elevated by FTCs, and relative higher rates of methane emissions were found for FTC2 to FTC15, compared to those from low altitude peatlands. Methane emissions were significantly correlated to the export of dissolved organic carbon (DOC), the activities of β-D-cellobiosidase and phenol oxidase in various freeze-thaw conditions. This study highlights the importance of FTCs in stimulating methane emissions and implies that methane emissions during FTCs from high altitude peatland would increase under a warmer climate in the future.